요양병원 진폐환자의 구강건강인식 조사 - 오나래(Na-Rae Oh); 윤성욱(Sung Uk Yoon); 정미애(Mi-Ae Jeong) (한국콘텐츠학회 논문지, 16(6), 2016)
This study was conducted to examine the oral health awareness, needs of dental treatment and the oral and maxillofacial pains targeting pneumoconiosis patients of care hospitals for the purpose of providing basic data for preparing a plan to improve the oral health of patients plagued with pneumoconiosis. As the subjects of survey, total 120 patients who have agreed to the research among the patients of three care hospitals, were enrolled between March and July in 2015. As the result of the study on the factors that influence the oral health perception, it was verified that the persons of an average monthly income of 2 million won or more, were shown to have significantly better oral health awareness than the subjects of monthly earning of less than 2 million won (p<0.05), thus showing that the oral health awareness by the people of monthly income of more than 2 million won, was 0.77 times higher compared to the others. Therefore, in order to improve the oral health awareness of pneumoconiosis patients, the economic stability of the patients should be taken into account as a priority when examining the oral health policy decisions and it was recommended that the survey and research on the oral health of patients with pneumoconiosis can be done in amore systematic manner. 본 연구는 요양병원의 진폐환자를 대상으로 구강건강인식 및 치과진료요구, 구강악안면통증을 조사하여 진폐환자의 구강건강을 증진시키기 위한 방안을 마련하는 기초자료를 제공하고자 시행하였다. 연구대상은 2015년 3월부터 7월 까지 3개 요양병원의 환자 중 연구목적에 동의한 120명을 대상으로 하였다. 연구 결과 구강건강인식에 영향을 주는 요인은 평균 월수입이 200만원 이상인 대상자가 200만원 미만인 대상자보다 구강건강 인식도가 유의하게 좋은 것으로 나타났으며(p<0.05) 이는 200만원 이상일 때 구강건강인식도가 0.77배 인 것으로 나타났다 따라서, 진폐환자의 구강건강인식의 향상을 위해서는 구강보건 정책 결정 시 경제적 안정이 우선적으로 고려되어야 한다고 생각되며 진폐환자의 구강건강에 대한 조사 및 연구가 좀 더 체계적으로 이뤄져야 할 것으로 사료되었다.